Path Attenuation and Source Characteristics during the 2019 Sichuan Changning Earthquake Sequence in China - Zhijun Jiang; Lei Zhang; Qi Zhang (Advances in Civil Engineering)
To give an insight into the path attenuation and source characteristics of the 2019 Sichuan Changning earthquake sequence, 99 strong-motion recordings at 33 stations were studied. The S-wave Fourier amplitude spectra were used to determine the path-attenuation function and key parameters of the seismic source characteristics of this sequence. The results show the following: (1) The geometric spreading effect presents hinged-trilinear characteristics, and the corresponding geometric spreading rates were −0.97, 0.29, and −0.73 with the crossover distances 90 km and 183 km. (2) The quality factor Q is correlated with frequency and expressed as 217 × f0.82 for the range from 0.1 to 10.0 Hz. (3) The seismic moment was inversely proportional to the cube of the corner frequency, and their product was 2.37 × 1016 N. m/s3. (4) The stress drop varied from 1.18 to 12.44 MPa. Both the attenuation effect and source parameters of this sequence are significantly different from those of the Lushan and the Wenchuan aftershock sequences in the Sichuan region of China.